Phylogenetic analysis of the long terminal repeat of feline immunodeficiency viruses from Japan, Argentina and Australia - Yamada, Hiroshi (1995)
The nucleotide sequences of the long terminal repeat of five Japanese, five Argentine and three Australian isolates of feline immunodeficiency virus (FIV) were determined and compared with those of isolates previously described. The results revealed that the Japanese isolates were found to cluster with nucleotide sequence similarity of 95.6%–99.4%. The Australian isolates also clustered with nucleotide sequence similarity of 97.2%–99.4%. The Argentine isolates formed two groups; the LP9 isolate is closely related to the Japanese isolates, whereas the LP1, LP3, LP20 and LP24 isolates are distant from both the Japanese and Australian isolates. From these results, FIV can be divided into three groups, namely: (I) the Californian, Australian and British isolates; (II) the Japanese isolates and one Argentine LP9 isolate; (III) the other Argentine isolates.